Pengembangan Penangkaran Bibit Lada di Kelompok Tani Desa Sukamarga, Lampung Utara - Suprapto Suprapto (Jurnal Penelitian Pertanian Terapan, 2011)
Development of pepper propagation variety Natar 1 in farmers' groups Sukamarga village, north Lampung since the year 2006 to 2010 through the stages (1) providing plant material for pepper seedlings with construct (a) the mother garden pepper in the field in 2000 stem, (b) holding a mini garden pepper 7600 stems at 3 locations and (2) the propagation pepper seedlings to order the farmer/user/ Plantation Office District/Province. Pepper cutting source Natar 1 of Experimental garden Cahaya Negeri (Balitro) with the guidance of captivity in the field of BPTP Lampung. Results pepper propagation during 2006-2010 in the mother garden pepper in the field and mini garden pepper produce pepper cuttings one node one leaf as 476,862 with a value of Rp119,215,500, -, have been made pepper seedlings ready to plant as many as Rp 1,834,000,- stem and has been sold Rp 1,746,000,- stem with a value Rp 6,221,000,000,-. Pepper seedlings Natar 1 largely for the mother garden pepper the mother garden pepper and rehabilitation garden pepper plants in North Lampung (1442,000 stem), East Lampung (304,000 stems), Central Lampung was 50,000 pepper cuttings and Way Kanan district 50 000 pepper cuttings. Buyer Natar 1 pepper seedlings were mainly from the Plantation Office and District Forestry and Plantation Office of Lampung Province. Keywords: Development, Pepper, Propagation; seedling, Natar 1, Farmers group.